Expert System Mediagnosa Hama On Phon Oil With Certainty Factor Method - Situmorang, Lamhot; Riandari, Fristi (Information Technology and Science (ITScience), 2020)
The process of palm oil culture is influenced by various factors, one of which is the pest and disease factors. Generally the problem of farmers differentiating pests and diseases, this is dyed most of the farmers lack information and rely on the experience of other farmers to overcome the existing pest and disease problems. In handling pests and diseases, it is necessary to have a farmer consilant who is able to diagnose pests and diseases on oil palm trees. In this study, an expert system for diagnosing pests and diseases in palm tree plants, as well as providing various solutions for pests or diseases. The method used in this expert system is the Certainty Fators method. Certainty Method The factors was chosen because this method is suitable in the process of determining the identification of pests and diseases and the result of this application is the percentage of the system. The percentage is influenced by the CF value obtained from the system, the percentage of expert system consultations is taken from the highest yield as an alternative to other pests or diseases that attack oil palm tree crops.